Supporting the next generation of non-communicable disease research leaders in Africa – experience of the GSK Africa NCD Open Lab - Juliet Addo; Mike Strange; Lindsay Kendall; Annie Stylianou; Sally Gatsi; Phyllis Guta; Rhona Scott; Agbor Ako (Journal of Global Health Reports)
# Background